Part 2 - Sudden cardiac death in athletes Focused cause-and-effect screening - Paterick, T. E.; Choudhary, N.; Chandrasekaran, K.; Tajik, A. J.; Seward, J. (Journal of Exercise, Sport & Orthopedics, 2015)
Sudden death in an athlete is a tragic event. There is a strong social imperative to implement effective means of predicting and preventing sudden death in athletes. However, the design and implementation of a solution seems unobtainable [2]. Part Two discusses how novel attributes of systems biology and digital technology are capable of delivering high quality, low cost athletic screening. The merit of a transformative idea does not necessarily predict its adoption. The greatest barrier to change lies in the acquiescence to familiar practices even in light of new ideas and technology. The current thought in athletic screening is more centered on specific disease associations (rule-in principle), [3-5] and much less about the sensitivity of pathophysiologic causality (ruleout principle) [5-8].